IMPLEMENTASI BIMBINGAN PRIBADI SOSIAL MELALUI GOOGLE MEET UNTUK PENYESUAIAN DIRI SISWA KELAS VII MTs AL-INAYAH KOTA BANDUNG - Aditiya, Muhammad Fakhrizal; Rukanda, Nandang; Fatimah, Siti (IKIP Siliwangi, 2024)
This research is motivated by the transition of students in the new school so that there are problems regarding adjustment. As a form of effort to handle the problem of adjustment, personal-social guidance services can be used as an alternative to improve good self-adjustment for students when entering a new school environment. Because of the personal-social guidance aims to assist students in directing the things that must be done when entering a new school environment. The purpose of this study was to determine the implementation of personal-social guidance services on students' self-adjustment, while the research method used in this study was a qualitative method. Instruments for collecting data in this study were observation, interviews and documentation. The subjects in this study were 3 students who had adjustment problems at school. The results of this study indicate that after being provided with personal-social guidance services there are several changes that are shown compared to before being provided with services. So that the implementation of personal-social guidance services through google meet is effective for the adjustment of class VII students at MTs Al-Inayah Bandung City.